Diversity of bird species in paddy habitat in Alus-alus of Simeulue Regency - Rika Susanti; Abdullah Abdullah; Devi Syafrianti; Muhibbuddin Muhibbuddin; Khairil Khairil (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Research entitled